Centro de artes y oficios Galarza - Camino Duarte, Zoraya (Universidad Antonio Nariño, 2023)
The objective of this research is to design an architectural proposal with optimal infrastructure, which responds to the needs of the population in the context of sex work in the Galarza park sector, with the purpose of training and promoting new sources of income, which contributes to their social rehabilitation. Through a descriptive investigation, an immersion in the place is carried out, recognizing the territory, examining the different dynamics of the place, and analyzing the reality from the experience of the main actors. It is found that there is a population of 210 sex workers who mostly practice this trade because it is the only economic support and that of their families, that 80% of these women suffer all kinds of violence, and that there has been an increase of figures of those who provide their sexual services in exchange for money, generating a social isolation that is increasing every day and a social exclusion that increasingly